Analisis Penyebab Oil Spill Dan Pelaksanaan Contigency Plan Dalam Penanganan Pencemaran di Laut - B.L Hentri Widodo; Eni Tri Wahyuni Wahyuni; Aan Rubiyanto (Politeknik Bumi Akpelni Semarang, 2025)
The purpose of this paper is to discuss the occurrence of oil spills at sea, handling of oil spills to prevent pollution of the marine environment. The causes of oil spills include ship operations including loading and discharging, grounding, collision, hull leaks, damage loading and unloading equipment, explosions or fires and other causes. Oil spills with a volume of 7-700 tons when collide 26 percent and due to ships aground 19 percent when ships are loading and unloading and bunkering. Oil spills a volume of >700 tons occurred when the collided 30 percent aground 31 percent. To reduce the impact of oil spills, the implementation of the oil spill contigency plan (OSCP) carried out. Implementation of the contigency plan include teamwork, data collection, assessment, use of equipment, supervision and monitoring, cooperation related parties and evaluation. The method is by collecting data by observation, and literature study. The discussion obtained data on the causes oil spills and countermeasures with contigency emergency plans. The resul this paper is analysis of the causes of oil spills and countermeasures. The conclusion is oil spills are caused by ship operations including ship accidents. And steps to minimize the potential for wider pollution by implementing an oil spill contigency plan.